Nasofacial zygomycosis: case report from Pará, Brazil - Moraes, Mário A. P.; Almeida, Margarida M. R.; Veiga, Regina Celi C.; Silveira, Fernando T. (Revista do Instituto de Medicina Tropical de São Paulo, 1994)
A case of nasofacial zygomycosis in a 64-year-old female patient from Barcarena, State of Pará, is reported. This is the second time that the disease is recognized in Northern Brazil. The diagnosis was initially suspected by the direct observation of broad coenocytic hyphae in biopsy specimens of the nasal cavity mucosa. Later, the cause of the disease was confirmed by the mycologial and histopathological findings. Rapid response to the therapy with potassium iodide was achieved, without however a complete resolution of the lesions. The patient still remains under treatment, with itraconazole and iodide